Magnitude of alimentary lipemia is related to intima-media thickness of the common carotid artery in middle-aged men. - Karpe, F; de Faire, U; Mercuri, M; Bond, MG; Hellénius, M; Hamsten, A (1998)
Fat intake leads to generation of potentially atherogenic triglyceride-rich lipoproteins (TRL). To investigate the relationship between early atherosclerotic changes and accumulation of hepatic and intestinal TRL after oral fat intake, an estimate of the intima-media thickness (IMT) was made using ultrasound of the common carotid artery, and postprandial TRL was quantified during a standardized oral fat tolerance test in 30 healthy normo- and hypertriglyceridemic middle-aged men. At base line the expected positive association between the LDL cholesterol level and the IMT of the common carotid artery was observed (r = 0.53, P<0.01). In addition, postprandial plasma triglycerides, in particular those measured late (6 h) after intake of the test meal, correlated positively with the IMT (r = 0.44, P<0.05). Of note, this latter correlation was independent of both the LDL cholesterol and the fasting plasma triglyceride concentrations. In a multivariate analysis, 39% of the total variability for the common carotid IMT were explained by age, LDL cholesterol and the postprandial triglyceride level. In univariate analysis, few statistically significant relations were found between common carotid IMT and postprandial levels of chylomicron remnants, VLDL and VLDL remnants of different particle size, the latter determined by specific measurements of ApoB-48 and ApoB-100 in subfractions of TRL. Therefore, in healthy middle-aged men, elevated postprandial triglyceride levels might identify a metabolic state related to early atherosclerosis.